2007
DOI: 10.1152/ajpheart.01335.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of polyol pathway to arteriolar dysfunction in hyperglycemia. Role of oxidative stress, reduced NO, and enhanced PGH2/TXA2 mediation

Abstract: Hyperglycemia increases glucose metabolism via the polyol pathway, which results in elevations of intracellular sorbitol concentration. Thus we hypothesized that elevated level of sorbitol contributes to the development of hyperglycemia-induced dysfunction of microvessels. In isolated, pressurized (80 mmHg) rat gracilis muscle arterioles (approximately 150 microm), high glucose treatment (25 mM) induced reduction in flow-dependent dilation (from maximum of 39 +/- 2% to 15 +/- 1%), which was significantly mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…This is in accordance with the reported restoration of NO production by AR inhibition in human umbilical endothelial cells cultured in a medium with high glucose content [40]. These assumptions are also supported by previous work in which ZOP inhibited the reduction in flow-induced dilation induced by high glucose [36] and restored NO production in ischemic myocardial injury [41]. In addition, FER improved the bioavailability of stimulated NO in the aortas isolated from spontaneously hypertensive rats [42].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with the reported restoration of NO production by AR inhibition in human umbilical endothelial cells cultured in a medium with high glucose content [40]. These assumptions are also supported by previous work in which ZOP inhibited the reduction in flow-induced dilation induced by high glucose [36] and restored NO production in ischemic myocardial injury [41]. In addition, FER improved the bioavailability of stimulated NO in the aortas isolated from spontaneously hypertensive rats [42].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…Our data indicated that both FER and ZOP significantly prevented the diminished relaxation to ACh in aortas isolated from animals with MetS without affecting the response to PE. This coincides with pprevious reports in which zopolrestat recover the high glucose-induced reduction of flow-induced dilation [36]. On the other hand, short-term in vitro incubation of aortas isolated from (+ 10% fructose) animals with FER and ZOP restored normal endothelial dependent relaxation.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 89%
“…5 and 6). A recently study (49) showed that increased endothelial sorbitol is a possible mechanism for the hyperglycemia-induced ROS and the resultant enhanced TP activation, resulting in impaired flow-mediated dilation. In addition, rosiglitazone treatment decreased NADPH oxidase activity but failed to complete restore superoxide levels, suggesting the possibility of other NADPH oxidase-independent ROS, which may account for the remained impairment in functional dilation after treatment in OZRs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the polyol pathway improves the function of SERCA and ryanodine receptor by protecting them from irreversible oxidation [67]. Besides the importance of aldose reductase in cardiac dysfunction under diabetes mellitus, aldose reductase has been implicated in the development of microvascular dysfunction during diabetes [68]. Inhibition of aldose reductase prevents protein kinase C and nuclear factor-κB activation induced by a variety of stimuli such as TNF-α, fibroblast growth factor-2, angiotensin II, and high glucose [69][70][71], suggesting that aldose reductase regulates stress responses and the activation of nuclear factor-κB and other protein kinase C-sensitive transcription factors.…”
Section: Hyperglycemiamentioning
confidence: 99%